Innovating with the past: challenges and opportunities for the Archive of Universitat Jaume I. Issue 1 (January 2020) - París-Folch, María-Lidón
Abstract : This article considers the challenges and opportunities that the current digital and open access context offers for the historical records which preserve institutional memory, through the experience and projects of the Archive of Universitat Jaume I (Castellón, Spain). The starting point is the records within the Archive: records of the University and from former higher educational institutions – Escuela de Magisterio and Colegio Universitario de Castellón (1900–1991) – along with other external holdings. These are indispensable information resources for research into university history, but they are also useful for researching subjects such as the evolution of teaching, economics, university life and for biographical study. In the current culture of "openness, " a context which includes European legislation on digitization and on heritage and using new concept of Digital Humanities, the Archive can respond to the new challenges and engage in innovative lines of work which are adding value to the historical records. Current projects of the university Archive are discussed, projects which recognize the importance of understanding the user, digitization, open access, dissemination and cooperation. These projects show that by expanding the traditional services it offers, a university archive can become a mainstay for learning, teaching and research within the institution, resulting in turn in more users and a new role.